Factors influencing medication adherence in co-morbid hypertension and diabetes patients: A scoping review - Adwoa Oforiwaa Kwakye; Irene A. Kretchy; Prince Peprah; Kofi Boamah Mensah (Elsevier, 2024)
Introduction: Interest in medication adherence has expanded significantly, especially in relation to the management of hypertension or diabetes in recent years. A scoping review that focuses on medication adherence in the co-morbidity of hypertension and diabetes provides crucial guidance for effective management of these interrelated diseases. Aim: To conduct a scoping review of factors associated with medication adherence among individuals with co-morbid hypertension and diabetes. Methods: The evaluation was conducted in accordance with the PRISMA-ScR guidelines to ensure the quality of the study. We searched three databases (Scopus, CINAHL, Medline) and one search engine (Google Scholar) from April 2023 to July 2023 on studies related to medication adherence in co-morbid hypertension and diabetes. Except for reviews there were no restrictions on design, location, and time of study. Results: In total, 972 studies that were not duplicated were obtained. After eligibility and screening procedures were completed, 31 articles were ultimately included in the scoping review. Medication adherence was significantly affected by patient, condition, therapy, socio-economic and health related factors. Intervention trials revealed that education and counselling by pharmacists, nurses, physicians, diabetes educators, community health workers and the use of telephone to motivate patients significantly improved medication adherence. Conclusion: This review shows the intricate factors influencing medication adherence in patients with co-morbid hypertension and diabetes, emphasizing the need for tailored interventions involving healthcare professionals, policymakers, and researchers.